TEMPORAL INFLUENCE OF NSAIDS ON MECHANICALLY INDUCED BONE FORMATION AND FLUID FLOW STIMULATED CELLULAR PGE2 PRODUCTION - Druchok, Cheryl (My University, 2016)
Prostaglandins (PGs) are important signalling factors for bone mechanotransduction. The inhibition of cyclooxygenase, responsible for the synthesis of PGs, with non-steroidal anti-inflammatory drugs (NSAIDs) has been shown to influence bone formation induced by mechanical stimulation. The purpose of this study was to examine the timing effects of NSAID administration on: 1) bone formation induced by multiple mechanical loading events in a rat model and 2) the PGE2 response of MLO-Y4 osteocyte like cells stimulated by fluid shear stress. The rat forelimb compression model was used to induce bone formation in male and female rats using a 1-month loading protocol (12 loading sessions). The right forelimbs were loaded and the left forelimbs served as non-loaded controls. NSAIDs were administered orally either before or after loading. Fluorochrome labels were administered to the rats to determine mineral apposition rate (MAR). The NSAIDs examined (indomethacin, NS-398 and ibuprofen) did not significantly affect periosteal MAR, administered either before or after loading, suggesting NSAIDs do not affect bone adaptation to multiple mechanical loading events. To examine in vitro effects of NSAIDs on PGE2 production, an orbital shaker was used to apply fluid shear stress to MLO-Y4 cells seeded in 6-well culture plates. Indomethacin was added to the culture media either before or after loading and media PGE2 concentrations were determined at various time points by enzyme immunoassay. Fluid shear stress increased PGE2 production of MLO-Y4 cells and indomethacin administration inhibited that response when administered both before and after fluid flow. However, PGE2 production was influenced by the media changes that occurred in the in vitro experiments, making it difficult to differentiate between indomethacin effects and media change effects. The in vitro experiments revealed the difficulties of modeling the timing effects of NSAID administration on MLO-Y4 PGE2 production in response to fluid flow.
Keywords: bone adaptation; NSAIDs; biomechanics; prostaglandin; fluid flow